PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI, SISTEM PENGENDALIAN INTERN DAN KOMITMEN ORGANISASI TERHADAP KINERJA INSTANSI PEMERINTAH (Studi Pada Satuan Kerja Perangkat Daerah Kota Payakumbuh) - Adif Putra Zodia; Kamaliah -; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the influence of information technology, the internal control system and organizational commitmenton on the SKPD performance. This study was conducted at SKPD of Payakumbuh city. The population in this study were employed who worked in the SKPD Payakumbuh city (30 government agencies). The sampling method used in this study is saturated sampling method. The respondent in this study is the head of SKPD, secretary of SKP, treasurer of SKPD and the head of financial, . The sample used in this study were 120 respondents. The hypotheses then tested is multiple linear regression analysis by using SPSS version 20.0 The result of this study indicated that the influence of information technology has not effect on SKPD performance. While the internal control system and organizational commitmenton has effect on SKPD performance. The magnitude of the effect (R2) the influence of information technology, the internal control system and organizational commitmenton on the SKPD performance area was 62,1%. While the remaining 37,9% is influenced by other independent variabel that are not observed in this study.Keywords: information, technology, internal control, commitmenton, performance.